Gambaran Pengetahuan Tentang Pencegahan Kekambuhan Pada Pasien Asma - Dian Kartikasari; Riesma Damayanti Finishia (Universitas Muhammadiyah Pekajangan Pekalongan, 2023)
Asthma is an inflammatory respiratory disease caused by narrowed airways resulting in wheezing, shortness of breath, and chest pain. Knowledge of asthma is essential to prevent asthma recurrence, so patients can avoid precipitating factors that can cause asthma recurrence. This study aims to describe the knowledge about the prevention of recurrence in asthma patients. This descriptive study used the accidental sampling technique and involved 41 patients treated at the Pulmonary Polyclinic at Bendan Hospital, Pekalongan City. The Tullu questionnaire was used. This study indicated that most patients seeking treatment at the Pulmonary Polyclinic at Bendan Hospital Pekalongan City had poor knowledge of 27 respondents (65.9%). In contrast, some patients have good knowledge and as many as 14 respondents (34.1%) regarding the prevention of asthma recurrence. The majority of respondents in this study have less knowledge. Therefore, intense health education about asthma is necessary to improve patients’ knowledge.Asthma is an inflammatory respiratory disease caused by narrowed airways resulting in wheezing, shortness of breath, and chest pain. Knowledge of asthma is essential to prevent asthma recurrence, so patients can avoid precipitating factors that can cause asthma recurrence. This study aims to describe the knowledge about the prevention of recurrence in asthma patients. This descriptive study used the accidental sampling technique and involved 41 patients treated at the Pulmonary Polyclinic at Bendan Hospital, Pekalongan City. The Tullu questionnaire was used. This study indicated that most patients seeking treatment at the Pulmonary Polyclinic at Bendan Hospital Pekalongan City had poor knowledge of 27 respondents (65.9%). In contrast, some patients have good knowledge and as many as 14 respondents (34.1%) regarding the prevention of asthma recurrence. The majority of respondents in this study have less knowledge. Therefore, intense health education about asthma is necessary to improve patients’ knowledge.